2007
DOI: 10.1101/sqb.2007.72.039
|View full text |Cite
|
Sign up to set email alerts
|

Principles and Problems Revolving Round Rhythm-related Genetic Variants

Abstract: Much of what is known about the regulation of circadian rhythms has stemmed from the induction, recognition, or manufacture of genetic variants. Such investigations have been especially salient in chronobiological analyses of Drosophila. Many starting points for elucidation of rhythmic processes operating in this insect entailed the isolation of mutants or the design of engineered gene modifications. Various features of the principles and practices associated with the genetic approach toward understanding cloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 120 publications
(155 reference statements)
0
2
0
Order By: Relevance
“…For example, altering or eliminating DOUBLETIME (DBT) kinase activity or replacing specific PER phosphorylation sites with non-phosphorylatable or phosphomimetic residues can drastically alter circadian period or eliminate oscillator function altogether, [6][7][8][9] demonstrating the need for post-translational control. Likewise, circadian oscillator function is impaired or abolished by eliminating per and tim mRNA cycling, 10,11 boosting CLOCK-CYCLE (CLK-CYC) transcriptional activity by adding a VP16 activation domain to CYC, 12 and eliminating a single E-box within the per promoter (JH Houl and PE Hardin), demonstrating the need for transcriptional control. These autoregulatory circuits provide a useful framework for describing circadian feedback loop function and the relationship between rhythmically expressed gene products ( Fig.…”
mentioning
confidence: 99%
“…For example, altering or eliminating DOUBLETIME (DBT) kinase activity or replacing specific PER phosphorylation sites with non-phosphorylatable or phosphomimetic residues can drastically alter circadian period or eliminate oscillator function altogether, [6][7][8][9] demonstrating the need for post-translational control. Likewise, circadian oscillator function is impaired or abolished by eliminating per and tim mRNA cycling, 10,11 boosting CLOCK-CYCLE (CLK-CYC) transcriptional activity by adding a VP16 activation domain to CYC, 12 and eliminating a single E-box within the per promoter (JH Houl and PE Hardin), demonstrating the need for transcriptional control. These autoregulatory circuits provide a useful framework for describing circadian feedback loop function and the relationship between rhythmically expressed gene products ( Fig.…”
mentioning
confidence: 99%
“…Again supporting the post-translational camp, Yang and Sehgal (2001) found that constitutive expression of per and tim could rescue the rhythmic behavior of per 01 ; tim 01 double null mutants. However, a recent reanalysis of this experiment indicates that the extent of rhythmicity was probably overestimated and most of the rhythms detected were weak (Hall et al 2007). However the strongest piece of evidence for a post-translational clock comes from Cyanobacteria, where circadian rhythms in phosphorylation of the KaiC clock protein can be seen for several days in a test tube when mixing three proteins together-with no DNA or RNA present (Nakajima et al 2005).…”
Section: Perspective: Transcriptional or Post-translational Regulation?mentioning
confidence: 99%